Strategi Badan Pengembangan Sumber Daya Manusia Provinsi Jawa Timur dalam Upaya Mencegah Kekerasan Berbasis Gender - Nur Amalia, Selvy; Rohman, Abid (VISA: Journal of Vision and Ideas, 2025)
This study aims to examine the strategy of the Human Resources Development Agency (BPSDM) of East Java Province in implementing Sustainable Development Goals 5.2, especially through the implementation of the ASN Learning Series 39 Program themed "The Role of Women in Mental Health and Prevention of Gender-Based Violence." The problem raised in this study is to what extent the ASN Learning Series 39 Program organized by the BPSDM of East Java Province can be said to be a form of implementation of sustainable development goals, especially SDG 5.2 which targets the elimination of all forms of violence against women and children in public and private spaces. The approach used is descriptive qualitative, with data collection techniques through interviews, documentation, and analysis of webinar materials. The study results show that this program reflects the implementation of SDG 5.2 through the delivery of educational materials, the involvement of cross-sector actors, and the strengthening of the role of ASN as agents of change.